Isolation, Identification, and Extraction of Probiotics from Bifidobacterium Bifidum - Hassan, Wassan Rodha; Alghanimi, Yasemin Khudiar; Al-Awade, Heyam Abdul Ridha (American Journal of Biology and Natural Sciences, 2024)
The current study aims to Isolation and identification of the Bifidobacterium bifidum isolates from different sources, including fresh cow’s milk, breastfeeding mothers’ milk, and imported and locally produced dairy products, and their comparison with the standard isolate. The Diffusion of Oils test and the Emulsification Index (E24) test were conducted to investigate the ability of Bifidobacterium bifidum to produce biosurfactants (BS). The biosurfactant was then extracted and freeze-dried using a lyophilizer. Which can later be used in many applications due to its unique properties and be widely used in the food and pharmaceutical industry as probiotics.